Binding of yeast killer toxin to a cell wall receptor on sensitive Saccharomyces cerevisiae. - Bussey, H (1979)
35S-labeled killer toxin protein bound to cells of sensitive Saccharomyces cerevisiae S14a. Strains that were resistant to toxin through mutation in the nuclear genes kre1 kre2 bound toxin only weakly. Non-radioactive toxin competed effectively with 35S-labeled toxin for binding to S14a, but did not compete significantly in the binding to mutant kre1-1. This implied that binding to kre1-1 was nonspecific. A Scatchard analysis of the specific binding to S14a gave a linear plot, with an association constant of 2.9 x 10(6) M-1 and a receptor number of 1.1 x 10(7) per cell. Killer toxin receptors were solubilized from the cell wall by zymolyase digestion. Soluble, non-dialyzable cell wall digest from S14a competed with sensitive yeast cells for 35S-labeled toxin binding and reduced toxin-dependent killing of a sensitive strain. Wall digest from kre1-1 competed only weakly for toxin binding with sensitive cells and caused little reduction of toxin-dependent killing. Although the abundant (1.1 x 10(7) per cell) receptor appeared necessary for toxin action, as few as 2.8 x 10(4) toxin molecules were necessary to kill a sensitive cell of S14a. The kinetics killing of S14a suggested that some component was saturated with toxin at a concentration 50-fold lower than that needed to saturate the wall receptor.